The importance of in-season strength and power training in football athletes: A brief review and recommendations - Yu, L.; Altieri, C.; Bird, S. P.; Corcoran, G.; Jiuxiang, G. (International Journal of Strength and Conditioning, 2021)
Football (soccer) performance requires a diversity of physical attributes and biomotorabilities, such as strength, power, jump mechanics, repeat sprint ability, change of direction and on-ball skills. In-season training focus is often based on metabolic conditioning activities such as small sided games, tactical and technical football drills and traditional running drills in order to further develop and maintain aerobic and anaerobic capacity. However, this often comes at the expense of strength training, which may be compromised for additional time on the pitch. Therefore, the purpose of this review is to provide an evidenced-based approach, to the periodisation of strength and power during a football season. Secondly, the increased popularity of incorporating on-pitch pre-rehabilitation and injury prevention programs that utilise unstable exercises during the entire season to maintain strength and power will also be discussed. Collectively, literature suggests that strength and power maintenance can be achieved with one strength session per week for football athletes. However, it is important for strength and conditioning coaches to continue the development of strength and power characteristics during a football season, which not only assists on-pitch performance but may also attribute to reduction of injury risk. Evidence supporting the effectiveness of on-pitch pre-rehabilitation programming centred on unstable training is lacking at this time.